Self-image, self-acceptance and the therapeutic effects among patients suffering from mental and physical diseases – comparative study - Zboralski, Krzysztof; Gałecki, Piotr; Orzechowska, Agata; Berent, Dominika; Talarowska, Monika (Current Problems of Psychiatry, 2011)
Aim: The aim of the study is to get to know about mutual relationships between individual self-imagine, level of self-acceptance and the therapeutic effects among patients who suffer from mental diseases and physical diseases.Material and methods: The study involved 97 people, divided into two groups: 41 patients with recurrent depressive disorder (first group) and 56 people treated for selected somatic disorders (gastrointestinal diseases, skin diseases and diabetes type 1 and type 2 – the second group). The personal questionnaire, Adjective Check List by H.G. Gough and A. B. Heilbrun (ACL) and Clinical Global Impression Scale (CGI) were used in the examination.Results: Statistically significant relationships between the analyzed variables were observed. The size of therapeutic effect is associated with the level of self-acceptance, and with positive self-image of the patients. Patients with higher levels of self-acceptance achieved greater improvement as a result of the treatment. Using this relationship applies to both patients somatically and mentally ill.Conclusions:• The size of therapeutic effect is associated with the level of self-acceptance and with the self-image of the patients.• Patients with higher levels of self-acceptance achieved greater improvement in the assessment of the treatment.• Using this relationship applied to both patients somatically and mentally ill.• Between patients with depression and somatic illness differences mainly concerned the current image, but there was a very similar ideal self-image.